1999
DOI: 10.1523/jneurosci.19-21-09538.1999
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Learning by EphA Receptors: a Protein Targeting Study

Abstract: EphA family receptor tyrosine kinases and their ephrin-A ligands are involved in patterning axonal connections during brain development, but until now a role for these molecules in the mature brain had not been elucidated. Here, we show that both the EphA5 receptor and its ephrin-A ligands (2 and 5) are expressed in the adult mouse hippocampus, and the EphA5 protein is present in a phosphorylated form. Because there are no pharmacological agents available for EphA receptors, we designed recombinant immunoadhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 66 publications
1
52
0
Order By: Relevance
“…Ephrin-A5 forward signaling to EphA receptors is me-diated by tetrameric or higher order cell surface EphA clustering (25,26). This is blocked by the EphA5-Fc construct (27)(28)(29)(30), as shown in the previous in vitro and in vivo studies. However, administering preclustered ephrin-A5-Fc will cluster EphA receptors, stimulate ephrin signaling, and mediate a gain of function in this growth inhibitory system within periinfarct cortex (7,27,(29)(30)(31).…”
Section: Resultssupporting
confidence: 57%
“…Ephrin-A5 forward signaling to EphA receptors is me-diated by tetrameric or higher order cell surface EphA clustering (25,26). This is blocked by the EphA5-Fc construct (27)(28)(29)(30), as shown in the previous in vitro and in vivo studies. However, administering preclustered ephrin-A5-Fc will cluster EphA receptors, stimulate ephrin signaling, and mediate a gain of function in this growth inhibitory system within periinfarct cortex (7,27,(29)(30)(31).…”
Section: Resultssupporting
confidence: 57%
“…The presence of a phosphorylated form of EphA5 receptor in the adult brain leads to the speculation about possible roles in synaptic plasticity (Gerlai et al, 1999). By infusing EphA5 receptor agonist/antagonist proteins into the hippocampus, Gerlai et al (1999) showed that activation of the EphA5 receptor enhances hippocampal-dependent behavioral tasks whereas the inactivation of the EphA5 receptor impairs these functions.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we found similar spine densities in sham wildtype and ephrin-A2 -/- mice, suggesting that if present, deficits in spines are subtle in ephrin-A2 -/- mice. Although ephrin-A2 is expressed in the mouse hippocampus throughout life and has been implicated in its topographic organisation 35, 36 , to our knowledge, there is no evidence that ephrin-A2 is involved in synaptic plasticity or spine dynamics. Rather, these processes involve ephrin-A3, ephrin-A5 and members of the ephrin-B family 37 .…”
Section: Discussionmentioning
confidence: 93%